2006
DOI: 10.1152/ajpgi.00450.2005
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses the expression of extracellular matrix genes in activated hepatic stellate cells by inhibiting gene expression of connective tissue growth factor

Abstract: Zheng, Shizhong, and Anping Chen. Curcumin suppresses the expression of extracellular matrix genes in activated hepatic stellate cells by inhibiting gene expression of connective tissue growth factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
69
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 56 publications
10
69
0
Order By: Relevance
“…24 Our recent results supported the proposal and demonstrated an antagonistic relationship between the activation of TGF-b signaling and the gene expression of PPARg in HSC. 24 The attention of the current study was paid to the role of PDGF and/or EGF signaling in the curcumin induction of PPARg gene expression in activated HSC. Results in this report demonstrated that exogenous PDGF or EGF caused a dosedependent reduction in PPARg gene expression in passaged HSC (Figure 1).…”
Section: Activating Pdgf and Egf Signaling Inhibits Pparc Expression supporting
confidence: 85%
See 4 more Smart Citations
“…24 Our recent results supported the proposal and demonstrated an antagonistic relationship between the activation of TGF-b signaling and the gene expression of PPARg in HSC. 24 The attention of the current study was paid to the role of PDGF and/or EGF signaling in the curcumin induction of PPARg gene expression in activated HSC. Results in this report demonstrated that exogenous PDGF or EGF caused a dosedependent reduction in PPARg gene expression in passaged HSC (Figure 1).…”
Section: Activating Pdgf and Egf Signaling Inhibits Pparc Expression supporting
confidence: 85%
“…Cells were serum-starved in DMEM for 48 h, which made cells more sensitive to serum stimulation. [22][23][24] Serum-starved cells were pretreated with curcumin for 30 min before the stimulation with FBS (10%) for an additional 20 min. Whole-cell extracts were prepared.…”
Section: Curcumin Reduces Tyrosine Phosphorylation Of Pdgf-br and Egfrmentioning
confidence: 99%
See 3 more Smart Citations